'Political' animals of Sakha Yakutia - Stammler-Gossmann Anna (Tohoku University. Center for Northeast Asian Studies, 2010)
Good to Eat, Good to Live with: Nomads and Animals in Northern Eurasia and Africa / edited by Florian Stammler, Hiroki Takakura. 2010 (Northeast Asian Study Series 11)